2014
DOI: 10.1536/ihj.14-190
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tolvaptan in Patients With Chronic Kidney Disease Due to Diabetic Nephropathy With Heart Failure

Abstract: SummaryThe efficacy of tolvaptan for treating heart failure has already been shown. Adequate data relating to the effect of tolvaptan on the correlation of water balance in renal disease are not available. A retrospective study was conducted on the efficacy and adverse reactions of tolvaptan for treating nephrotic syndrome.The subjects were 26 patients with chronic kidney failure due to diabetic nephropathy with heart failure who were administered tolvaptan and seen between December 2011 and October 2013. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 22 publications
1
25
0
Order By: Relevance
“…Sato, et al demonstrated in a recent study that some responders with diabetes mellitus nephropathy received a clinical benefit from TLV treatment even though their renal dysfunction was approximately equivalent to stage G4 CKD (22.1 ± 18.1 mL/minute/1.73m 2 of estimated glomerular filtration ratio). 4) Among the 8 patients from whom renal specimens were obtained, 7 were responders and simultaneously had explicit expression of aquaporin-2 (AQP2) in the collecting ducts. The remaining patient was a non-responder showing no expression of AQP2 with histological evidence of tubulointerstitial damage.…”
Section: Article P533mentioning
confidence: 99%
See 1 more Smart Citation
“…Sato, et al demonstrated in a recent study that some responders with diabetes mellitus nephropathy received a clinical benefit from TLV treatment even though their renal dysfunction was approximately equivalent to stage G4 CKD (22.1 ± 18.1 mL/minute/1.73m 2 of estimated glomerular filtration ratio). 4) Among the 8 patients from whom renal specimens were obtained, 7 were responders and simultaneously had explicit expression of aquaporin-2 (AQP2) in the collecting ducts. The remaining patient was a non-responder showing no expression of AQP2 with histological evidence of tubulointerstitial damage.…”
Section: Article P533mentioning
confidence: 99%
“…However, how can we measure the expression of AQP2 in the human kidney? Sato, et al obtained renal biopsy specimens and demonstrated the expression of AQP2 immunohistologically, 4) but such an invasive procedure is rarely feasible, especially in patients with coagulopathy due to hepatic congestion or those treated with anticoagulants. We recently proposed urine AQP2 (U-AQP2) as a novel noninvasive marker to predict responses to TLV.…”
Section: Article P533mentioning
confidence: 99%
“…In general, expression of AQP-2 decreases in patients with CKD (8). We have reported that AQP-2 immunostaining is absent in renal tissues of tolvaptan non-responders with diabetic nephropathy but expressed strongly in responders (11). In the present cases, AQP-2 was expressed strongly in the renal tissue of the tolvaptan responder (Case 1) but only weakly in the non-responder (Case 2).…”
Section: Discussionmentioning
confidence: 95%
“…AQP-2 immunohistochemistry was performed via the following method (polymer technique): The kidney tissues were fixed in 20% neutral buffered formalin and embedded in paraffin, and sections 2-3 μm in thickness were prepared. The details of the method have been reported previously (11). Briefly, the simple statin MAX-PO (MULTI) (NICHIREI BIOSCIENCES INC., Tokyo, Japan) Polymer reagent instillation was performed as follows: incubation at room temperature for 30 minutes, and then washing with TBS for 5 minutes, 3 times.…”
Section: Case Reportmentioning
confidence: 99%
“…Finally, the effects of tolvaptan treatment in patients with moderate to severe renal dysfunction warrant further evaluation. 22) Conclusions: Tolvaptan therapy provided body weight reduction mainly via high-volume diuresis in most patients, and about 80% of the patients were identified as clinical responders. However, this therapy was insufficient for symptom relief and hemodynamic improvement in a minority of the patients.…”
Section: Figure 2 Amentioning
confidence: 98%